Analisis Kinerja Pelayanan Dan Harapan Pada Pengunjung Museum Jateng Ranggawarsita - Vera Marlia Puspita; Hardi Warsono; Margaretha Suryaningsih (Journal of Public Policy and Management Review, 2014)
Analysis databases must address satisfying service, analysis of the level of interest of the elements of the service received, and identify elements of the service is a priority to improve service quality in Central Java Museum Ranggawarsita is absolutely necessary for the improvement of the quality of existing services in Central Java Museum Ranggawarsita. There are 22 indicators used to assess quality of care, 22 indicators were then analyzed using Cartesian diagram. So as to know the map indicator/dimension level of service between the level of service performance and the level of interest in Java Ranggawarsita Museum visitors.